[2,6-Bis(6-methylquinolin-2-yl)pyridine-kappa N-3,N `,N `']dichloridoiron(II) - Li, Xiao-Ping; Zhao, Jian-She; Ng, S.W. (International Union of Crystallography, 2010)
In the molecule of the title compound, [FeCl2(C25H19N3)], the three N atoms span the axial-equatorial-axial sites of the trigonal-bipyramidal coordination polyhedron; the geometry of the Fe-II atom is 32% distorted from trigonal-bipyramidal (towards square-pyramidal along the Berry pseudorotation pathway). One of the Cl atoms is disordered over two positions in a 0.938 (11):0.062 (11) ratio. Intermolecular C-H center dot center dot center dot Cl hydrogen bonding occurs in the crystal structure.